2011
DOI: 10.2147/jir.s19461
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines regulate endothelial cell survival and tissue repair functions via NF-κB signaling

Abstract: Inflammation contributes to the development of fibrotic and malignant diseases. We assessed the ability of inflammatory cytokines to modulate endothelial cell survival and functions related to tissue repair/remodeling. Treatment with interleukin (IL)-1β or tumor necrosis factor (TNF)-α (2 ng/mL) led to human pulmonary artery endothelial cells becoming spindle-shaped fibroblast-like cells. However, immunoblot and DNA microarray showed no change in most endothelial and mesenchymal markers. In the presence of IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…We have previously reported that inflammatory cytokines IL-1β and TNF-α modulate endothelial cell survival through p65 activation [4] and that p38 modulates endothelial cell survival and tissue repair function in response to IL-1β stimulation [17]. In the current study, we further report that TNF-α also induced MAPK (ERK, JNK, and p38) activation; furthermore, MAPK kinase inhibitors can also modulate endothelial cell survival.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…We have previously reported that inflammatory cytokines IL-1β and TNF-α modulate endothelial cell survival through p65 activation [4] and that p38 modulates endothelial cell survival and tissue repair function in response to IL-1β stimulation [17]. In the current study, we further report that TNF-α also induced MAPK (ERK, JNK, and p38) activation; furthermore, MAPK kinase inhibitors can also modulate endothelial cell survival.…”
Section: Discussionsupporting
confidence: 71%
“…We recently reported that TNF-α can promote HPAEC survival and tissue repair functions including wound closure and collagen gel contraction [4]. The mechanism by which the effect of TNF-α is mediated, however, has not been defined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations